Kecerdasan Emosional Terhadap Kinerja Karyawan di Kantor Camat Dakopemean - Aqfir; Moh.Sabran A; Burhanuddin (Jurnal Multidisiplin Madani, 2022)
This study aims to determine and analyze the effect of emotional intelligence on employee performance at the Dako Pemean sub-district office, Tolitoli Regency. This type of causality research with a quantitative approach. Data collection techniques using questionnaires. The population in this study were all employees at the Dako Pemean sub-district office, Tolitoli Regency, amounting to 30 people. The technique of determining the sample uses the census method in which the entire population is used as a respondent. The analysis tool is simple linear regression. The results of this study obtained R Square with a positive and significant value which indicates a unidirectional effect, which means emotional intelligence has a significant effect on employee performance at the Dako Pemean District Office, Tolitoli Regency, the rest is influenced by other variables not examined in this study.